Magnetic carrier, two-component developer, and replenishment developer
By using a coating composed of resin A and resin B of specific structures on the magnetic carrier, the wear resistance and charge retention problems caused by toner adhesion and mechanical load during long-term use are solved, and the consistency and stability of image density are achieved, and the service life of the carrier is extended.
Patent Information
- Application Number
- JP2021029395
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-02-26
AI Technical Summary
During long-term use, existing magnetic carriers are prone to reduce charge sites and color changes due to the adhesion of toner components. At the same time, the wear resistance of the coating under mechanical load is insufficient, resulting in core material exposure, affecting charge retention and image quality.
A magnetic carrier coating containing resin A and resin B is adopted. The head and side chains and two side chain structures of resin A are used to reduce the surface energy of the coating and reduce the adhesion of toner components through specific partial structures and SP values. At the same time, resin B has a high affinity with the two side chains of resin A, which enhances the wear resistance of the coating.
It realizes the consistency and stability of image density under high humidity environment and long-term use, reduces the adhesion of toner components and the wear of coating, extends the service life of the carrier, and improves image quality.
Smart Images

Figure 0007657609000040 
Figure 0007657609000041 
Figure 0007657609000042
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic carrier, a two-component developer, and a replenishment developer, which are used in an image forming method for visualizing an electrostatic image by electrophotography. [Background technology]
[0002] Conventionally, in the electrophotographic image forming method, a method is generally used in which an electrostatic latent image is formed on an electrostatic latent image carrier by using various means, and toner is attached to the electrostatic latent image to develop it. In this development, a two-component development method is widely adopted in which carrier particles called magnetic carrier are mixed with the toner, and the toner is triboelectrically charged to give an appropriate amount of positive or negative charge to the toner, and the charge is used as a driving force for development. In the two-component development method, functions such as stirring, transporting, and charging the developer can be imparted to the magnetic carrier, so the division of functions between the magnetic carrier and the toner is clear, and this has the advantage of good controllability of developer performance. Here, the magnetic carrier often has a core that is magnetized to obtain transportability, and a resin coating that provides the ability to impart charge to the toner. In recent years, technological advances in the field of electrophotography have created demands for greater durability of the main body, and the carrier is required to maintain its charge imparting ability even after long-term use. However, it is generally known that the charge imparting ability of a carrier decreases due to the adhesion of toner components to a carrier, resulting in a decrease in the number of charge sites, resulting in image problems such as changes in color. As a means for obtaining the above-mentioned durability against adhesion of toner components (hereinafter referred to as contamination resistance), there is an example in which a material with low surface free energy, such as a fluororesin, is used as a coating resin (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 63-235963 [Patent Document 2] Japanese Patent Application Publication No. 53-97435 [Patent Document 3] Japanese Patent Application Publication No. 2-186360 Summary of the Invention [Problem to be solved by the invention]
[0004] However, generally, materials with low surface free energy such as fluororesin can suppress adhesion of toner components, but have weak molecular interactions and are easily broken by external forces. For this reason, if fluororesin is used for the carrier coating layer, there is a concern that the wear resistance of the coating layer will decrease due to mechanical loads generated during stirring and transport in the developing machine. In addition, there is a concern that the core material of the carrier (hereinafter also referred to as the carrier core), which is a low-resistance component, will be exposed, causing a decrease in charge and a decrease in charge retention. Furthermore, low surface free energy materials such as fluororesins have poor adhesion to the core material of the carrier (hereinafter also referred to as the carrier core), and an external force may cause film peeling at the interface between the core material and the coating layer. In order to reduce the wear and peeling of the coating layer, it is possible to graft-copolymerize multiple fluororesins, such as fluorinated alkyl (meth)acrylates, but this structure still leaves the coating layer with insufficient wear resistance and adhesion to the core material (Patent Document 2). In addition, in order to improve wear resistance, it is possible to use it in combination with other (meth)acrylate copolymers (hereinafter also referred to as blends) (Patent Document 3). However, in order to improve contamination resistance, measures such as including 50% by mass or more of fluorinated alkyl (meth)acrylates are necessary, and it is thought that wear resistance will not improve significantly. In the above example, the reason why 50% or more by mass of fluorinated alkyl (meth)acrylate is required is that when fluorinated alkyl (meth)acrylate is blended with other acrylate copolymers, the interaction between the acrylic parts is strong, so that the acrylic parts attract each other, and the fluorinated alkyl group parts tend to aggregate exclusively. It is considered that the exclusively aggregated fluorinated alkyl group parts cannot contribute to low surface free energy (stain resistance). For this reason, in order to ensure sufficient stain resistance, the blend must have a high ratio of fluorinated alkyl (meth)acrylate, which is considered to result in insufficient abrasion resistance. In other words, to realize a highly stable, long-life carrier, it is necessary to achieve both high levels of contamination resistance, which prevents toner components from adhering, and abrasion resistance, which prevents the coating from wearing down due to mechanical loads. In view of the above, an object of the present invention is to provide a carrier capable of reducing image changes caused by contamination of toner components and image changes caused by carrier wear even during long-term use. [Means for solving the problem]
[0005] The carrier of the present invention is a magnetic carrier having a magnetic carrier core and a coating resin layer that coats the surface of the magnetic carrier core, The coating resin layer contains a resin A and a resin B, The coating resin layer is all Based on the resin component, the content of the resin A is 1.0% by mass or more and 50.0% by mass or less, and the content of the resin B is 50.0% by mass or more and 99.0% by mass or less, The resin A is The main chain and a first side chain bonded to the main chain and having a partial structure represented by any one of formulas (1) to (3); a second side chain attached to the backbone; and It has When the total mass of the first side chains in the resin A is a1 and the total mass of the second side chains is a2, the a1 and a2 are 0.02≦a1 / a2≦2.00 Fulfilling When the SP value of the first side chain is SPa1, the SP value of the second side chain is SPa2, and the SP value of the resin B is SPb1, the SPa1, SPa2, and SPb1 are: 1.3 <SPa2-SPa1≦7.0 1.3 <SPb1-SPa1≦7.0 0.0≦|SPa2-SPb1|≦1.3 The magnetic carrier is characterized by satisfying the above.
[0006] [ka] (In the above formula (1), R 1 represents a hydrogen or a methyl group. X 1 stands for "COO" or "O". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0007] [ka] (In the above formula (2), R 11 indicates "OCH3", or "OC2H5" or "CH3". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0008] [ka] (In the above formula (3), R 13 indicates "F" or "H". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less. The developer of the present invention is a two-component developer comprising the magnetic carrier and toner. The replenishing developer of the present invention is a replenishing developer comprising the above magnetic carrier and toner. Effect of the Invention
[0009] According to the present invention, there is provided a magnetic carrier capable of outputting a stable image density even after long-term use, with uniform image density, and even when left in a high-humidity environment. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram of an image forming apparatus suitable for forming an image using the present invention. [Diagram 2] FIG. 1 is a schematic diagram of an image forming apparatus suitable for forming a full-color image using the present invention. [Diagram 3] FIG. 2 is a schematic diagram of a surface treatment device suitable for surface treatment of the toner for the developer of the present invention. [Figure 4]FIG. 2 is a schematic diagram of a resistivity measuring device used in the magnetic carrier core of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified.
[0012] The magnetic carrier of the present invention is a magnetic carrier having a magnetic carrier core and a coating resin layer that coats the surface of the magnetic carrier core, The coating resin layer contains a resin A and a resin B, Based on the resin components constituting the coating resin layer, the content of the resin A is 1.0% by mass or more and 50.0% by mass or less, and the content of the resin B is 50.0% by mass or more and 99.0% by mass or less, The resin A is The main chain and a first side chain bonded to the main chain and having a partial structure represented by any one of formulas (1) to (3); a second side chain attached to the backbone; and It has When the total mass of the first side chains in the resin A is a1 and the total mass of the second side chains is a2, the a1 and a2 are 0.02≦a1 / a2≦2.00 Fulfilling When the SP value of the first side chain is SPa1, the SP value of the second side chain is SPa2, and the SP value of the resin B is SPb1, the SPa1, SPa2, and SPb1 are: 1.3 <SPa2-SPa1≦7.0 1.3 <SPb1-SPa1≦7.0 0.0≦|SPa2-SPb1|≦1.3 The present invention is characterized in that it satisfies the following:
[0013] [ka] (In the above formula (1), R1 represents a hydrogen or a methyl group. X 1 stands for "COO" or "O". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0014] [ka] (In the above formula (2), R 11 indicates "OCH3", or "OC2H5" or "CH3". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0015] [ka] (In the above formula (3), R 13 indicates "F" or "H". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0016] <Carrier coating resin> The carrier of the present invention comprises resin A and resin B, and resin A has a first side chain having a fluorinated alkyl group structure and a second side chain having a structure other than an alkyl fluoride structure. The fluorinated alkyl group structure of the first side chain has low affinity with the second side chain, and resin B has a composition that has low affinity with the fluorinated alkyl group structure of the first side chain and high affinity with the second side chain.
[0017] The fluorinated alkyl group structure of the first side chain has low affinity with the second side chain and resin B, so the fluorinated alkyl group structure portion of resin A is less likely to have affinity with other structural portions and is more likely to be oriented on the magnetic carrier surface. As a result, the surface free energy of the magnetic carrier is lowered, and the adhesion and fixation of toner-derived components can be reduced. This makes it possible to reduce the decrease in the charging ability of the magnetic carrier, charging variations, and changes in developer fluidity caused by toner-derived components over a long period of time without changing the developer, and suppress variations in image density in high-density images.
[0018] In addition, the high affinity between the second side chain of resin A and resin B strengthens the entanglement of the molecules of resin A and resin B, and the wear resistance can be improved. This reduces the exposure of the magnetic carrier core, which is a low resistance site. As a result, it is possible to prevent charge leakage from the low resistance site without replacing the developer for a long time, and even if the electrophotographic machine main body is not operated for a long period of time, the reproducibility of density gradation can be maintained. Furthermore, since the second side chain and resin B are not fluorinated alkyl group structures, the adhesion with the magnetic carrier core is also higher than that of conventional fluorine-containing coated carriers. If the adhesion with the magnetic carrier core decreases, the coat peels off, and the magnetic carrier core, which is a low resistance site, becomes more exposed. As a result, in high density image areas, there is a concern that the magnetic carrier particles will fly together with the toner by following the development electric field of the toner (hereinafter referred to as carrier flying).
[0019] In addition, the relationship between the total mass of the first side chains and the total mass of the second side chains is also important, and a specific mass ratio can achieve both stain resistance and abrasion resistance. If the mass ratio of the first side chains is too low, stain resistance tends to decrease, and if the mass ratio of the first side chains is too high, abrasion resistance tends to decrease.
[0020] Furthermore, both contamination resistance and abrasion resistance can be achieved by setting the mass ratio of resin A to resin B to a specific ratio. If the mass ratio of resin A is low, contamination resistance tends to decrease, and if the mass ratio of resin A is high, abrasion resistance tends to decrease.
[0021] In the present invention, the resin A has a first side chain having a first partial structure represented by any one of the above formulas (1) to (3). The above formula (1) indicates that the main chain of the resin A is an acrylic skeleton, the above formula (2) indicates that it is a silicone skeleton, and the above formula (3) indicates that it is a fluorinated alkyl skeleton.
[0022] In the above formula (1), R 1 represents hydrogen or a methyl group, and X 1 In the above formula (2), R 11indicates "OCH3", "OC2H5", or "CH3", and R 2 is the same as in formula (1). In formula (3), R 13 indicates "F" or "H", and R 2 is the same as the above formula (1).
[0023] R 2 represents an alkyl group having 1 to 20 carbon atoms, and the alkyl group may be a halogen-substituted alkyl group in which at least a part of hydrogen atoms are substituted with fluorine atoms, or a halogen-substituted alkyl group in which a part of the remaining hydrogen atoms are substituted with halogen atoms other than fluorine atoms. In addition, based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the halogen-substituted alkyl group, the ratio of fluorine atoms is 5.0 atomic % or more, and the ratio of halogen atoms other than fluorine atoms is 40.0 atomic % or less. As a specific introduction method, for example, when polymerizing resin A, it is possible to introduce it by copolymerizing an acrylic acid ester or a methacrylic acid ester in which a halogen-substituted alkyl structure is esterified.
[0024] In the present invention, the content of the resin A is 1.0% by mass or more and 50.0% by mass or less, and the content of the resin B is 50.0% by mass or more and 99.0% by mass or less, based on the resin components constituting the coating resin layer. More preferably, the content of the resin A is 4.0% by mass or more and 40.0% by mass or less, and the content of the resin B is 60.0% by mass or more and 96.0% by mass or less. By being in this range, the contamination resistance and abrasion resistance are improved, but if the amount of the resin A is small, the effect of reducing adhesion originating from the toner components is small, and there is a possibility that the uniformity of the image density is affected. Also, if the amount of the resin A is large, the adhesion between the magnetic carrier core and the coating layer is reduced, and the influence of peeling of the coat, etc. becomes a concern. As a result, in a high-density image part, the phenomenon that the magnetic carrier particles fly together with the toner (hereinafter referred to as carrier flying) becomes a concern.
[0025] In the magnetic carrier of the present invention, when the total mass of the first side chain is a1 and the total mass of the second side chain is a2, 0.02 ≦ a1 / a2 ≦ 2.00. More preferably, 0.03 ≦ a1 / a2 ≦ 1.00. Thereby, variation in image density in a high-concentration image can be suppressed, and reproducibility of density gradation can be maintained even during a period when the electrophotographic apparatus main body is not operated for a long time.
[0026] In the magnetic carrier of the present invention, when the SP value of the first side chain is SPa1 and the SP value of the second side chain is SPa2, 1.3 < SPa2 - SPa1 ≦ 7.0. Preferably, 2.0 ≦ SPa2 - SPa1 ≦ 6.0. Also, when the SP value of resin B is SPb1, 1.3 < SPb1 - SPa1 ≦ 7.0. Preferably, 1.4 < SPb1 - SPa1 ≦ 6.0, and more preferably 1.5 < SPb1 - SPa1 ≦ 6.0. This indicates that the fluorinated alkyl group structure of the first side chain has low affinity with the second side chain and resin B, and within the above range, variation in image density in a high-concentration image can be suppressed.
[0027] Also, in the carrier of the present invention, 0.0 ≦ |SPa2 - SPb1| ≦ 1.3, preferably 0.0 ≦ |SPa2 - SPb1| ≦ 1.2, and more preferably 0.0 ≦ |SPa2 - SPb1| ≦ 1.1. This indicates that the second side chain structure of resin A has high affinity with resin B, and as a result, even during a period when the electrophotographic apparatus main body is not operated for a long time, reproducibility of density gradation can be maintained. Also, carrier flight can be suppressed.
[0028] The SP value is calculated by the following method. Formula: SP value = √(Ev / v) = √(ΣΔei / ΣΔvi) In the formula, Ev: evaporation energy (J / mol), v: molar volume (cm 3 / mol), Δei: evaporation energy of each atom or atomic group, Δvi: molar volume of each atom or atomic group)
[0029] When the main chain of resin A is an acrylic skeleton, it is preferable for the first side chain having the first partial structure represented by formula (1) above to have at least any of the structures represented by formulas (1-1) to (1-4) below in order to achieve both stain resistance and abrasion resistance.
[0030] [ka] (In the above formulas (1-1) to (1-4), R 1 X represents a hydrogen atom or a methyl group. 1 stands for "COO" or "O". 21 R represents a single bond or an alkylene group. 22 Rf represents an alkylene group having a branched structure formed by a carbon-carbon bond. 11 Rf represents a monovalent group having at least a fluoroalkyl group. 12 Rf represents a fluoroalkyl group having a tertiary or quaternary carbon. 13 represents a perfluoroalkyl group having 4 to 6 carbon atoms.
[0031] In the magnetic carrier of the present invention, when the main chain of resin A is an acrylic skeleton and the skeleton of the second side chain is acrylic, it is preferable for the second side chain to have a partial structure represented by the following formula (4) in order to achieve both contamination resistance and abrasion resistance.
[0032] [ka] (R 3 R represents H or a methyl group. 4 represents a divalent organic group. X 2 represents a polymer having as a polymerization component one or more compounds selected from the group consisting of a hydrocarbon group having 6 to 1000 carbon atoms, or an acrylic acid ester, a methacrylic acid ester, styrene, and acrylonitrile.
[0033] Among these, R 4 As the divalent organic group, those having the structure shown below are more preferable. "O-CH2-CH(OH)-CH2-COO-CH2-S" "O-(CH2)2-CH(OH)-(CH2)2-COO-CH2-S" "O-(CH2)2" "COO"
[0034] Moreover, it is preferable that Resin B contains a resin containing a partial structure represented by the following formula (5).
[0035] [ka] (R 5 represents H or a methyl group, and Y represents a hydrocarbon group with 1 to 12 carbon atoms, "COOH", or "COOR" 6 " and R 6 represents a hydrocarbon group having 1 to 12 carbon atoms.
[0036] Formula (5) can be introduced by copolymerizing the following monomers. Specific examples include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, cyclobutyl acrylate, cyclohexyl acrylate, cyclopentyl acrylate, cyclooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, cyclobutyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, cyclooctyl methacrylate, and styrene. The above monomers may be copolymerized alone or in combination of two or more.
[0037] In the magnetic carrier of the present invention, when the main chain of resin A is an acrylic skeleton, it is preferable that the main chain has a partial structure represented by the following formula (6).
[0038] [ka] (R 7 represents "H" or "CH3", Z represents a hydrocarbon group with 1 to 12 carbon atoms, "COOH", or "COOR" 8 " and R 8It represents a hydrocarbon group having 1 to 12 carbon atoms.
[0039] Formula (6) can be introduced by copolymerizing the following monomers. Specific examples include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, cyclobutyl acrylate, cyclohexyl acrylate, cyclopentyl acrylate, cyclooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, cyclobutyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, cyclooctyl methacrylate, and styrene. The above monomers may be copolymerized alone or in combination of two or more.
[0040] In the magnetic carrier of the present invention, when the main chain of resin A is a silicone skeleton and the skeleton of the second side chain is silicone-based, it is preferable for the first side chain to have a partial structure represented by the following formula (2), and for the second side chain and resin B to contain a resin containing a partial structure represented by the following formula (7) in order to achieve both contamination resistance and abrasion resistance.
[0041] [ka] (In formula (2), R 11 indicates "OCH3", "OC2H5", or "CH3". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of the hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, and based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0042] [ka] (R9 or R 10 stands for "CH3" or "C6H5".)
[0043] In the magnetic carrier of the present invention, when the main chain of resin A is a fluoroalkyl skeleton and the skeleton of the second side chain is silicone-based, it is preferable for the first side chain to have a partial structure represented by the following formula (3), and for the second side chain and resin B to contain a resin containing a partial structure represented by the following formula (7) in order to achieve both contamination resistance and abrasion resistance.
[0044] [ka] (In the above formula (3), R 13 indicates "F" or "H". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of the hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, and based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
[0045] [ka] (R 9 or R 10 represents "CH3" or "C6H5".)
[0046] The total amount of the coating resins, Resin A and Resin B, of the magnetic carrier of the present invention is preferably 0.2 parts by mass or more and 5.0 parts by mass or less, based on 100 parts by mass of the magnetic carrier core, in order to achieve both contamination resistance and abrasion resistance, and more preferably 0.5 parts by mass or more and 4.0 parts by mass or less.
[0047] Furthermore, the coating resin layer of the present invention can contain conductive fine particles in the coating resin. The conductive fine particles can appropriately control the resistivity of the electrophotographic carrier. The content of the conductive fine particles added to the coating resin is preferably 0.1 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the coating resin. Examples of the conductive fine particles include carbon black, titanium oxide, and silver.
[0048] In addition, the coating resin may contain fine particles for the purpose of increasing the ability to impart charge to the toner and improving the releasability. The fine particles contained in the coating resin layer may be fine particles of either organic or inorganic materials, but crosslinked resin fine particles or inorganic fine particles having the strength to maintain the shape of the fine particles when coated are preferred. Examples of crosslinked resins forming crosslinked resin fine particles include crosslinked polymethyl methacrylate resins, crosslinked polystyrene resins, melamine resins, guanamine resins, urea resins, phenolic resins, and nylon resins. Examples of inorganic fine particles include silica, alumina, titania, etc.
[0049] The content of the fine particles in the coating resin layer is preferably 0.1 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the coating resin.
[0050] The copolymer of resin A and resin B of the present invention can be produced by a known polymerization method, specifically, a bulk polymerization method, a solution polymerization method, a suspension polymerization method, etc.
[0051] <Carrier core and its manufacturing method> For the magnetic carrier core of the present invention, known magnetic particles such as magnetite particles, ferrite particles, magnetic material-dispersed resin particles, etc. can be used. Among them, magnetic particles obtained by filling the pores of porous magnetic particles with a resin or magnetic material-dispersed resin particles, i.e., magnetic particles containing a magnetic oxide and a resin composition, are preferred from the viewpoint of extending the life since they can reduce the specific gravity of the magnetic carrier.
[0052] Reducing the specific gravity of the magnetic carrier reduces the load on the toner in the developer state in the developing device, prevents the adhesion of toner components to the magnetic carrier surface, reduces the load on the carriers themselves, and further suppresses peeling, chipping, and scraping of the coating resin layer. It also improves dot reproducibility, making it possible to obtain high-definition images.
[0053] In addition, the resin contained in the pores of the porous magnetic particles can be a copolymer resin used as a coating resin, but is not limited to this and can be any known resin. As the thermoplastic resin, the copolymer used as the coating resin is preferable, but other examples include the following. Polystyrene, polymethyl methacrylate, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyvinylidene fluoride resin, fluorocarbon resin, perfluorocarbon resin, solvent-soluble perfluorocarbon resin, polyvinylpyrrolidone, petroleum resin, novolac resin, saturated alkyl polyester resin, polyethylene terephthalate, polybutylene terephthalate, aromatic polyester resin such as polyarylate, polyamide resin, polyacetal resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyphenylene sulfide resin, polyether ketone resin.
[0054] Examples of thermosetting resins include the following: phenol resins, modified phenol resins, maleic resins, alkyd resins, epoxy resins, acrylic resins, unsaturated polyesters obtained by polycondensation of maleic anhydride, terephthalic acid, and polyhydric alcohols, urea resins, melamine resins, urea-melamine resins, xylene resins, toluene resins, guanamine resins, melamine-guanamine resins, acetoguanamine resins, glyptal resins, furan resins, silicone resins, polyimides, polyamideimide resins, polyetherimide resins, and polyurethane resins.
[0055] As a method for filling the voids of the ferrite particles having a porous shape with a resin component, there is a method of diluting the resin component in a solvent and adding the diluted solution to the porous magnetic core particles. The solvent used here may be any solvent capable of dissolving each resin component. In the case of a resin soluble in an organic solvent, an organic solvent such as toluene, xylene, cellosolve butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, or methanol may be used. In the case of a water-soluble resin component or an emulsion-type resin component, water may be used. As a method for adding a resin component diluted with a solvent to the inside of the porous magnetic core particles, there is a method of impregnating the resin component by a coating method such as a dipping method, a spraying method, a brush coating method, a fluidized bed method, or a kneading method, and then volatilizing the solvent. In the case of filling with a thermosetting resin, after volatilizing the solvent, the temperature is raised to the temperature at which the resin used hardens, and a hardening reaction is carried out.
[0056] On the other hand, specific methods for producing magnetic material-dispersed resin particles include the following. For example, submicron magnetic materials such as iron powder, magnetite particles, and ferrite particles are kneaded so as to disperse them in a thermoplastic resin, pulverized to a desired carrier particle size, and, if necessary, subjected to a thermal or mechanical spheroidizing treatment to obtain the particles. It is also possible to produce the magnetic material-dispersed resin particles by dispersing the magnetic material in a monomer and polymerizing the monomer to form a resin.
[0057] In this case, the resin may be a vinyl resin, a polyester resin, an epoxy resin, a phenol resin, a urea resin, a polyurethane resin, a polyimide resin, a cellulose resin, a silicone resin, an acrylic resin, or a polyether resin. The resin may be one type or a mixture of two or more types. In particular, a phenol resin is preferable in terms of increasing the strength of the carrier core. The true density and resistivity can be adjusted by adjusting the amount of the magnetic material. Specifically, in the case of magnetic particles, it is preferable to add 70% by mass or more and 95% by mass or less to the carrier.
[0058] The carrier core preferably has a volume average particle size (D50) of 20 μm to 80 μm in order to allow the coating resin to be uniformly coated, prevent carrier adhesion, and ensure an appropriate density of the developer magnetic brush to obtain high quality images.
[0059] The resistivity of the carrier core is 1.0×10 at an electric field strength of 1000 (V / cm). 5 (Ω cm) or more 1.0×10 14 (Ω·cm) or less is preferable because good developability can be obtained.
[0060] <Method of coating with resin> The method of coating the carrier core surface with the coating resin is not particularly limited, and can be performed by a known method. For example, there is a so-called immersion method in which the carrier core and the coating resin solution are stirred while volatilizing the solvent, and the carrier core surface is coated with the coating resin. Specific examples include a universal mixer (manufactured by Fuji Paudal Co., Ltd.) and a Nauta Mixer (manufactured by Hosokawa Micron Co., Ltd.). There is also a method in which the coating resin solution is sprayed from a spray nozzle while forming a fluidized bed, and the carrier core surface is coated with the coating resin. Specific examples include a Spiracoater (manufactured by Okada Seiko Co., Ltd.) and a Spiraflow (manufactured by Freund Corporation). There is also a method in which the coating resin is coated in a particle state on the magnetic carrier core in a dry manner. Specific examples include a treatment method using an apparatus such as a Hybridizer (manufactured by Nara Machinery Co., Ltd.), a Mechanofusion (manufactured by Hosokawa Micron Co., Ltd.), a HighFlex Gral (manufactured by Fukae Powtec Co., Ltd.), and a Theta Composer (manufactured by Tokuju Kogyo Co., Ltd.).
[0061] <Magnetic carrier> Next, the magnetic carrier will be described.
[0062] The magnetic carrier has a magnetization strength of 40Am under a magnetic field of 5000 / 4π(kA / m). 2 / kg or more 80Am 2 / kg or less. When the magnetization strength of the magnetic carrier is within the above range, the magnetic binding force to the developing sleeve is appropriate, so that the occurrence of carrier adhesion can be suppressed more effectively. In addition, the stress applied to the toner in the magnetic brush can be reduced, so that the deterioration of the toner and adhesion to other members can be suppressed more effectively.
[0063] The magnetization strength of the magnetic carrier can be adjusted by the amount of resin contained. The residual magnetization of the magnetic carrier is 20.0 Am 2 / kg or less, and 10.0Am 2 When the residual magnetization of the magnetic carrier is within the above range, particularly good fluidity is obtained as a developer, and good dot reproducibility is obtained.
[0064] The magnetic carrier has a true density of 2.5 g / cm 3 More than 5.5g / cm 3 It is preferable that the content is 3.0 g / cm or less. 3 More than 5.0g / cm 3 It is more preferable that the true density is within this range. A two-component developer containing a magnetic carrier having a true density within this range exerts a small load on the toner, and adhesion of the toner components to the magnetic carrier is suppressed. In addition, in order to achieve both good developability at low electric field strength and prevention of carrier adhesion, a true density within this range is preferable for the magnetic carrier.
[0065] The magnetic carrier preferably has a volume average particle size (D50) of 21 μm or more and 81 μm or less from the viewpoints of the ability to charge the toner, the suppression of carrier adhesion to the image area, and high image quality, and more preferably has a volume average particle size (D50) of 25 μm or more and 60 μm or less.
[0066] Next, methods for measuring various physical properties of the carrier will be described.
[0067] <Method for measuring volume average particle size (D50) of magnetic carrier> The particle size distribution was measured using a laser diffraction / scattering particle size distribution measuring device "Microtrac MT3300EX" (manufactured by Nikkiso Co., Ltd.).
[0068] The volume average particle size (D50) of the magnetic carrier was measured using a sample supply device for dry measurements, the "One-Shot Dry Sample Conditioner Turbotrac" (manufactured by Nikkiso Co., Ltd.). The supply conditions for the Turbotrac were a dust collector used as the vacuum source, with an air volume of approximately 33 l / sec and a pressure of approximately 17 kPa. Control was performed automatically on the software. The particle size was calculated as the 50% particle size (D50), which is the cumulative value of the volume average. Control and analysis were performed using the accompanying software (version 10.3.3-202D). The measurement conditions were as follows: SetZero time: 10 seconds Measurement time: 10 seconds Number of measurements: 1 Particle refractive index: 1.81% Particle shape: non-spherical Measurement upper limit: 1408μm Measurement lower limit: 0.243μm Measurement environment: 23℃, 50% RH
[0069] <Measurement of specific resistance of magnetic carrier> The resistivity value of the magnetic carrier is measured using the measuring device shown in FIG.
[0070] The resistivity is measured by filling the cell E with carrier, arranging a lower electrode and an upper electrode so as to be in contact with the carrier particles 1, applying a voltage between these electrodes, and measuring the current that flows at that time to obtain the resistivity. The measurement conditions for the resistivity in the present invention are: contact area S between the filled carrier and the electrodes = approximately 2.4 cm 2The sample thickness d is approximately 0.2 cm, and the load on the upper electrode is 240 g (2.35 N). Voltage is applied in the order of conditions (I), (II), and (III), and the current at the applied voltage under condition (III) is measured. The sample thickness d is then accurately measured, and the resistivity (Ω·cm) at each electric field strength (V / cm) is calculated, and the resistivity at an electric field strength of 3000 V / cm is taken as the resistivity of the sample's magnetic carrier. Application conditions (I): (Change from 0V to 1000V: Increase in steps of 200V every 30 seconds) (II): (1000V hold for 30 seconds) (III): (Change from 1000V to 0V: Decrease in steps of 200V every 30 seconds) Magnetic carrier resistivity (Ω cm) = (applied voltage (V) / measured current (A)) × S (cm 2 ) / d(cm) Electric field strength (V / cm) = applied voltage (V) / d (cm)
[0071] The resistivity of magnetite fine particles used in the magnetic material dispersion type resin carrier was also measured in the same manner.
[0072] <Method of measuring the magnetization strength of the carrier core> The magnetization strength of the carrier core can be measured by a vibrating sample magnetometer or a direct current magnetization characteristic recorder (BH tracer). In the examples described later, the magnetization strength is measured by a vibrating sample magnetometer BHV-30 (manufactured by Riken Denshi Co., Ltd.) according to the following procedure.
[0073] A cylindrical plastic container is filled with carrier cores sufficiently densely to prepare a sample. The actual mass of the sample filled in the container is measured. Then, the sample is adhered in the plastic container with instant adhesive so that the sample does not move.
[0074] Using a standard sample, the external magnetic field axis and the magnetization moment axis are calibrated at 5000 / 4π (kA / m).
[0075] The magnetization intensity was measured from the loop of the magnetization moment when an external magnetic field of 5000 / 4π (kA / m) was applied at a sweep speed of 5 (min / roop). From this, the magnetization intensity of the carrier core (Am 2 / kg).
[0076] <Measurement of true specific gravity of magnetic carrier core> The true specific gravity of the magnetic carrier particles can be determined by a dry automatic density meter, an autopycnometer.
[0077] <Separation of the coating resin layer from the magnetic carrier and separation of the coating resins A and B in the coating resin layer> As a method for separating the coating resin layer from the magnetic carrier, there is a method in which the magnetic carrier is placed in a cup and the coating resin is eluted with toluene.
[0078] The eluted resin is dried and then dissolved in tetrahydrofuran (THF) and separated using the following apparatus. [Device configuration] LC-908 (Japan Analytical Industry Co., Ltd.) JRS-86 (same company; repeat injector) JAR-2 (same company; autosampler) FC-201 (Gilson; Fraction Collector) [Column configuration] JAIGEL-1H~5H (20φ×600mm: preparative column) (Japan Analytical Industry Co., Ltd.) [Measurement conditions] Temperature: 40℃ Solvent: THF Flow rate: 5ml / min. Detector: RI
[0079] Based on the molecular weight distribution of the coating resin, the resin composition is specified by the following method, and the elution times at which the peak molecular weight (Mp) of coating resin A and coating resin B are reached are measured in advance, and the resin components are separated around that time. The solvent is then removed, and the resin is dried to obtain coating resin A and coating resin B.
[0080] In addition, the atomic groups can be identified from the absorption wave numbers using a Fourier transform infrared spectrometer (Spectrum One: manufactured by PerkinElmer), and the resin structures of the coating resin A and the coating resin B can be identified. Furthermore, the detailed structure can be identified using NMR (nuclear magnetic resonance spectroscopy).
[0081] <Quantitative Determination of Coating Amount of Carrier Coating Resin> The measurement equipment used is the AQF-100 automatic sample combustion device (manufactured by Mitsubishi Chemical) and the ICS-2000 ion chromatograph (manufactured by Dionex). The measurement principle is to burn the sample in the automatic sample combustion device, and to use hydrogen peroxide (H2O2) as an absorption liquid to extract the fluorine element in the fluororesin. - and PO4 3- is used as an internal standard substance, and quantitative determination is performed by ion chromatography.
[0082] The measurement conditions for the automatic sample combustion apparatus AQF-100 (manufactured by Mitsubishi Chemical Corporation) are as follows. InletTemp.; 900℃ OutletTemp.;1000℃ Ar / O2; 200ml / min O2: 400ml / min 1st position; 150mm / 60s End Time;360s Cool Time;30s BoatSpeed: 10mm / s The measurement conditions for the ion chromatograph ICS-2000 (Dionex Corporation) are as follows: It is. Separation column: AG12A / AS12A Injection volume: 25μl Eluent: 1 mM → 40 mM (20 min) gradient using an eluent generator The dissolution method is used. Flow rate;1.0ml / min Column oven: 35℃
[0083] Next, the constitution of the toner which is used together with the carrier as a two-component developer or a replenishing developer in the present invention and which is preferable for achieving the purpose will be described in detail below.
[0084] <Binding resin> The toner particles in the present invention may use the following polymers as the binder resin. Homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-based copolymers, such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, and styrene-methacrylic acid ester copolymer; styrene-based copolymer resin, polyester resin, a mixture of polyester resin and vinyl resin, or a hybrid resin in which both are partially reacted; polyvinyl chloride, phenol resin, naturally modified phenol resin, naturally modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane, polyamide resin, furan resin, epoxy resin, xylene resin, polyethylene resin, and polypropylene resin. Among these, polyester resin is preferably used as the main component from the viewpoint of low-temperature fixability.
[0085] As the monomers used in the polyester unit of the polyester resin, polyhydric alcohols (divalent or trivalent or higher alcohols), polyvalent carboxylic acids (divalent or trivalent or higher carboxylic acids), their acid anhydrides or their lower alkyl esters are used. Here, in order to create a branched polymer in order to express "strain hardening", it is effective to partially crosslink the amorphous resin molecule, and for this purpose, it is preferable to use a polyfunctional compound having a valence of three or more. Therefore, it is preferable to include a trivalent or higher carboxylic acid, its acid anhydride or its lower alkyl ester, and / or a trivalent or higher alcohol as the raw material monomer of the polyester unit.
[0086] As the polyhydric alcohol monomer used in the polyester unit of the polyester resin, the following polyhydric alcohol monomers can be used.
[0087] Examples of the dihydric alcohol component include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, and bisphenol represented by formula (A) and its derivatives;
[0088] [ka] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.)
[0089] Diols represented by formula (B);
[0090] [ka]
[0091] Examples of trihydric or higher alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. Among these, glycerol, trimethylolpropane, and pentaerythritol are preferably used. These dihydric alcohols and trihydric or higher alcohols can be used alone or in combination.
[0092] As the polybasic carboxylic acid monomer used in the polyester unit of the polyester resin, the following polybasic carboxylic acid monomers can be used.
[0093] Examples of divalent carboxylic acid components include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.
[0094] Examples of trivalent or higher carboxylic acids, their anhydrides or their lower alkyl esters include 1,2,4-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their anhydrides or their lower alkyl esters. Among these, 1,2,4-benzenetricarboxylic acid, i.e., trimellitic acid or its derivatives, is particularly preferred because it is inexpensive and easy to control the reaction. These divalent carboxylic acids and trivalent or higher carboxylic acids can be used alone or in combination.
[0095] The method for producing the polyester unit of the present invention is not particularly limited, and a known method can be used. For example, the above-mentioned alcohol monomer and carboxylic acid monomer are simultaneously charged, and polymerized through an esterification reaction or an ester exchange reaction and a condensation reaction to produce a polyester resin. The polymerization temperature is not particularly limited, but is preferably in the range of 180°C to 290°C. For the polymerization of the polyester unit, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. In particular, the binder resin of the present invention is more preferably a polyester unit polymerized using a tin-based catalyst.
[0096] In addition, it is preferable from the viewpoint of fogging that the acid value of the polyester resin is 5 mgKOH / g or more and 20 mgKOH / g or less, and the hydroxyl value is 20 mgKOH / g or more and 70 mgKOH / g or less, since this reduces the amount of moisture adsorption in a high temperature and high humidity environment and keeps the anti-electrostatic adhesion low.
[0097] The binder resin may be a mixture of a low molecular weight resin and a high molecular weight resin. The content ratio of the high molecular weight resin to the low molecular weight resin is preferably 40 / 60 or more and 85 / 15 or less on a mass basis from the viewpoint of low temperature fixability and hot offset resistance.
[0098] <Release agent> Examples of waxes that can be used in the toner of the present invention include the following: hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes containing fatty acid esters as the main component such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Further examples include the following. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene Saturated fatty acid bisamides such as bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0099] Among these waxes, from the viewpoint of improving low-temperature fixing property and fixing separation property, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax. In the present invention, the hydrocarbon waxes are more preferred from the viewpoint of further improving hot offset resistance.
[0100] In the present invention, the wax is preferably used in an amount of 3 parts by mass or more and 8 parts by mass or less per 100 parts by mass of the binder resin.
[0101] In addition, in an endothermic curve during temperature rise measured by a differential scanning calorimetry (DSC) device, the peak temperature of the maximum endothermic peak of the wax is preferably 45° C. or more and 140° C. or less. If the peak temperature of the maximum endothermic peak of the wax is within the above range, it is preferable because it is possible to achieve both storage stability and hot offset resistance of the toner.
[0102] <Coloring agent> The toner particles in the present invention may contain a colorant. Examples of the colorant include the following.
[0103] Examples of black colorants include carbon black, yellow colorants, magenta colorants, and cyan colorants used to tone the color to black. Although a pigment may be used alone as the colorant, it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of image quality of a full-color image.
[0104] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0105] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0106] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.
[0107] Dyes for cyan toners include CI Solvent Blue 70.
[0108] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20.
[0109] Yellow toner dyes include CI Solvent Yellow 162.
[0110] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency on an OHP sheet, and dispersibility in a toner.
[0111] The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less based on the total amount of the resin components.
[0112] <Inorganic fine particles> The toner preferably contains inorganic fine particles for the main purpose of improving fluidity and chargeability, and the inorganic fine particles are preferably attached to the toner surface.
[0113] As inorganic fine particles serving as spacer particles for improving the releasability between the toner and the carrier, silica particles having a maximum peak particle size based on the number distribution of 80 nm to 200 nm are preferred, and in order to function as spacer particles while better suppressing detachment from the toner, a particle size of 100 nm to 150 nm is more preferred.
[0114] In order to improve the fluidity of the toner, it is preferable to contain inorganic fine particles having a maximum peak particle size based on the number distribution of 20 nm to 50 nm, and it is also preferable to use them in combination with the silica particles.
[0115] Further, in order to improve the fluidity and transferability, other external additives may be added to the toner particles. The external additive added to the surface of the toner particles preferably contains inorganic fine particles such as titanium oxide, alumina oxide, and silica, and a plurality of types may be used in combination.
[0116] The total content of the external additives is preferably 0.3 parts by mass to 5.0 parts by mass, more preferably 0.8 parts by mass to 4.0 parts by mass, based on 100 parts by mass of toner particles. Among them, the content of silica particles having a maximum peak particle size of 80 nm to 200 nm based on the number distribution standard is 0.1 parts by mass to 2.5 parts by mass, more preferably 0.5 parts by mass to 2.0 parts by mass. Within this range, the effect as a spacer particle is more remarkable.
[0117] The surfaces of silica particles or inorganic fine particles used as external additives are preferably subjected to a hydrophobic treatment, which is preferably carried out with a coupling agent such as various titanium coupling agents or silane coupling agents, a fatty acid or a metal salt thereof, silicone oil, or a combination thereof.
[0118] Examples of titanium coupling agents include the following: tetrabutyl titanate, tetraoctyl titanate, isopropyl triisostearoyl titanate, isopropyl tridecylbenzenesulfonyl titanate, and bis(dioctyl pyrophosphate)oxyacetate titanate.
[0119] Examples of silane coupling agents include the following: γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)γ-aminopropyltrimethoxysilane hydrochloride, hexamethyldisilazane, methyltrimethoxysilane, butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, phenyltrimethoxysilane, o-methylphenyltrimethoxysilane, and p-methylphenyltrimethoxysilane.
[0120] Examples of fatty acids include long-chain fatty acids such as undecylic acid, lauric acid, tridecylic acid, dodecylic acid, myristic acid, palmitic acid, pentadecylic acid, stearic acid, heptadecylic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid. Examples of metals in the fatty acid metal salts include zinc, iron, magnesium, aluminum, calcium, sodium, and lithium.
[0121] Examples of silicone oils include dimethyl silicone oil, methylphenyl silicone oil, and amino-modified silicone oil.
[0122] The hydrophobic treatment is preferably carried out by adding a hydrophobic treatment agent to the particles to be treated in an amount of 1% by mass or more and 30% by mass or less (more preferably 3% by mass or more and 7% by mass or less) relative to the particles to be treated, thereby coating the particles to be treated.
[0123] The degree of hydrophobization of the hydrophobized external additive is not particularly limited, but for example, the hydrophobization degree after the treatment is preferably from 40 to 98. The hydrophobization degree indicates the wettability of a sample with respect to methanol, and is an index of hydrophobicity.
[0124] When the toner of the present invention is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio is 2% by mass or more and 15% by mass or less, preferably 4% by mass or more and 13% by mass or less, in terms of the toner concentration in the developer. If the toner concentration is less than 2% by mass, the image density tends to decrease, and if it exceeds 15% by mass, fogging and scattering in the machine tend to occur.
[0125] In addition, in a replenishing developer to be replenished to a developing device in response to a decrease in the toner concentration of the two-component developer in the developing device, the amount of toner is 2 parts by mass or more and 50 parts by mass or less per part by mass of the replenishing magnetic carrier.
[0126] Next, an image forming apparatus equipped with a developing device using the magnetic carrier, two-component developer and replenishment developer of the present invention will be described by way of example, but the developing device used in the developing method of the present invention is not limited to this.
[0127] <Image forming method> In FIG. 1, the electrostatic latent image carrier 1 rotates in the direction of the arrow in the figure. The electrostatic latent image carrier 1 is charged by a charger 2, which is a charging means, and the surface of the charged electrostatic latent image carrier 1 is exposed by an exposure device 3, which is an electrostatic latent image forming means, to form an electrostatic latent image. The developing device 4 has a developing container 5 that contains a two-component developer, and the developer carrier 6 is arranged in a rotatable state, and a magnet 7 is contained inside the developer carrier 6 as a magnetic field generating means. At least one of the magnets 7 is installed so as to be in a position facing the latent image carrier. The two-component developer is held on the developer carrier 6 by the magnetic field of the magnet 7, and the amount of the two-component developer is regulated by a regulating member 8, and the developer is transported to a developing section facing the electrostatic latent image carrier 1. In the developing section, a magnetic brush is formed by the magnetic field generated by the magnet 7. Thereafter, a developing bias consisting of an alternating electric field superimposed on a direct current electric field is applied, and the electrostatic latent image is visualized as a toner image. The toner image formed on the electrostatic latent image carrier 1 is electrostatically transferred to a recording medium (transfer material) 12 by a transfer charger 11. Here, as shown in FIG. 2, the image may be once transferred from the electrostatic latent image carrier 1 to an intermediate transfer body 9, and then electrostatically transferred to the recording medium 12.
[0128] Thereafter, the recording medium 12 is conveyed to a fixing device 13, where the toner is fixed onto the recording medium 12 by applying heat and pressure. Thereafter, the recording medium 12 is discharged outside the apparatus as an output image. After the transfer process, the toner remaining on the electrostatic latent image carrier 1 is removed by a cleaner 15. Thereafter, the electrostatic latent image carrier 1 cleaned by the cleaner 15 is electrically initialized by light irradiation from a pre-exposure device 16, and the above image forming operation is repeated.
[0129] FIG. 2 is a schematic diagram showing an example of the image forming method of the present invention applied to a full-color image forming apparatus.
[0130] The arrangement of the image forming units such as K, Y, C, and M in the figure, and the arrows indicating the rotation direction are not limited to those shown. Incidentally, K means black, Y means yellow, C means cyan, and M means magenta. In FIG. 2, the electrostatic latent image carriers 1K, 1Y, 1C, and 1M rotate in the direction of the arrows in the figure. Each electrostatic latent image carrier is charged by the chargers 2K, 2Y, 2C, and 2M, which are charging means, and the surface of each charged electrostatic latent image carrier is exposed by the exposure devices 3K, 3Y, 3C, and 3M, which are electrostatic latent image forming means, to form an electrostatic latent image. After that, the electrostatic latent image is visualized as a toner image by the two-component developer carried on the developer carriers 6K, 6Y, 6C, and 6M provided in the development devices 4K, 4Y, 4C, and 4M, which are development means. Furthermore, it is transferred to the intermediate transfer body 9 by the intermediate transfer chargers 10K, 10Y, 10C, and 10M, which are transfer means. The image is then transferred to a recording medium 12 by a transfer charger 11, which is a transfer means, and the recording medium 12 is heated and pressure fixed by a fixing device 13, which is a fixing means, and output as an image. An intermediate transfer body cleaner 14, which is a cleaning member for the intermediate transfer body 9, collects the toner remaining after transfer. Specifically, the development method of the present invention is preferably performed in a state where an AC voltage is applied to the developer carrier to form an alternating electric field in the development area while the magnetic brush is in contact with the photosensitive body. The distance (SD distance) between the developer carrier (developing sleeve) 6 and the photosensitive drum is 100 μm or more and 1000 μm or less, which is good for preventing carrier adhesion and improving dot reproducibility. If it is narrower than 100 μm, the supply of the developer is likely to be insufficient, and the image density is low. If it exceeds 1000 μm, the magnetic field lines from the magnetic pole S1 spread, the density of the magnetic brush is low, and the dot reproducibility is deteriorated, and the force binding the magnetic coated carrier is weakened, making it easy for carrier adhesion to occur.
[0131] The peak-to-peak voltage (Vpp) of the alternating electric field is 300V or more and 3000V or less, preferably 500V or more and 1800V or less. The frequency is 500Hz or more and 10000Hz or less, preferably 1000Hz or more and 7000Hz or less, and each can be appropriately selected and used depending on the process. In this case, the waveform of the AC bias for forming the alternating electric field can be a triangular wave, a rectangular wave, a sine wave, or a waveform with a changed duty ratio. In order to respond to changes in the toner image formation speed, it is preferable to apply a development bias voltage (intermittent AC superimposed voltage) having a discontinuous AC bias voltage to the developer carrier to perform development. If the applied voltage is lower than 300V, it is difficult to obtain a sufficient image density, and the fog toner in the non-image area may not be well collected. If it exceeds 3000V, the latent image may be disturbed through the magnetic brush, resulting in a decrease in image quality.
[0132] By using a two-component developer having a well-charged toner, the fog removal voltage (Vback) can be lowered, and the primary charge of the photoconductor can be lowered, thereby extending the life of the photoconductor. Although Vback depends on the development system, it is recommended that it be 200V or less, more preferably 150V or less. The contrast potential is preferably 100V or more and 400V or less to obtain sufficient image density.
[0133] In addition, if the frequency is lower than 500 Hz, the process speed is also affected, but the configuration of the electrostatic latent image bearing photoreceptor may be the same as that of a photoreceptor generally used in an image forming apparatus. For example, a photoreceptor having a configuration in which a conductive layer, an undercoat layer, a charge generating layer, a charge transport layer, and, if necessary, a charge injection layer are provided in this order on a conductive substrate such as aluminum or SUS.
[0134] The conductive layer, undercoat layer, charge generating layer and charge transport layer may be layers that are generally used in photoconductors. As the outermost layer of the photoconductor, for example, a charge injection layer or a protective layer may be used.
[0135] <Toner manufacturing method> The method for producing toner particles is not particularly limited, but a pulverization method is preferred from the viewpoint of dispersing the release agent and the polymer in which a styrene-acrylic polymer is graft-polymerized onto a polyolefin. The reason is that when toner particles are produced in an aqueous medium, the release agent, which is highly hydrophobic, and the polymer in which a styrene-acrylic polymer is graft-polymerized onto a polyolefin tend to be localized inside the toner particles. Therefore, it becomes difficult to form a core-shell structure by the above-mentioned heat treatment device.
[0136] The procedure for producing the toner by the pulverization method will be described below.
[0137] In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, colorant, crystalline polyester, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrids (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0138] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.
[0139] The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.
[0140] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).
[0141] Thereafter, the toner particles are surface-treated by heating to increase the circularity of the toner. For example, the surface treatment can be performed by hot air using a surface treatment device shown in FIG.
[0142] The mixture supplied by the material supply means 31 is introduced into an introduction pipe 33, which is installed vertically to the material supply means, by compressed gas adjusted by a compressed gas adjustment means 32. The mixture passing through the introduction pipe is uniformly dispersed by a conical protruding member 4 installed in the center of the material supply means, and is introduced into eight supply pipes 35 that radiate outward, and then into a treatment chamber 6 where heat treatment is carried out.
[0143] At this time, the flow of the mixture supplied to the treatment chamber is regulated by a regulating means 39 for regulating the flow of the mixture provided in the treatment chamber, so that the mixture supplied to the treatment chamber is heat-treated while swirling in the treatment chamber, and then cooled.
[0144] Hot air for heat-treating the supplied mixture is supplied from hot air supplying means 37, and is introduced into the treatment chamber by spirally swirling the hot air using a swirling member 43 for swirling the hot air. The configuration is such that the swirling member 43 for swirling the hot air has a plurality of blades, and the swirling of the hot air can be controlled by the number and angle of the blades. The hot air supplied into the treatment chamber preferably has a temperature of 100°C to 300°C at the outlet of the hot air supplying means 37. If the temperature at the outlet of the hot air supplying means is within the above range, it is possible to uniformly spheronize the toner particles while preventing the toner particles from fusing or coalescing due to excessive heating of the mixture.
[0145] The heat-treated toner particles are then cooled by cold air supplied from cold air supply means 38, and the temperature of the cold air supplied from cold air supply means 38 is preferably -20°C to 30°C. If the temperature of the cold air is within the above range, the heat-treated toner particles can be efficiently cooled, and the fusion and coalescence of the heat-treated toner particles can be prevented without impeding the uniform spheroidization of the mixture. The absolute moisture content of the cold air is 0.5 g / m 3 More than 15.0g / m 3 It is preferable that:
[0146] Next, the cooled heat-treated toner particles are collected by the collecting means 40 at the bottom end of the processing chamber. A blower (not shown) is provided ahead of the collecting means, so that the toner particles are sucked and transported by the blower.
[0147] The powder particle supply port 44 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 40 of the surface treatment device is provided on the outer periphery of the treatment chamber so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 38 is configured to be supplied from the outer periphery of the device to the circumferential surface inside the treatment chamber in a horizontal and tangential direction. The swirling direction of the toner supplied from the powder supply port, the swirling direction of the cold air supplied from the cold air supply means, and the swirling direction of the hot air supplied from the hot air supply means are all the same. Therefore, no turbulence occurs in the treatment chamber, the swirling flow in the device is strengthened, a strong centrifugal force is applied to the toner, and the dispersibility of the toner is further improved, so that a toner with a uniform shape and few coalesced particles can be obtained.
[0148] When the average circularity of the toner is 0.960 or more and 0.980 or less, the non-electrostatic adhesion can be kept low, which is preferable from the viewpoint of suppressing fogging.
[0149] Then, the fine powder side is divided into two parts, one for fine powder and the other for coarse powder. For example, the two parts are divided into two parts using an inertial classification system, Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.). A desired amount of silica fine particles A is externally added to the surface of each of the two heat-treated toner particles. Examples of the method of externally adding the toner particles include a method of stirring and mixing using a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external adder. In this case, an external additive other than silica fine particles, such as a fluidizing agent, may be externally added, if necessary.
[0150] Next, methods for measuring various physical properties of the toner and raw materials will be described below.
[0151] <Method of measuring weight average particle diameter (D4) and number average particle diameter (D1) of toner> The weight-average particle size (D4) and number-average particle size (D1) of the toner were measured using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data. Measurements were made with an effective measurement channel count of 25,000 channels, and the measurement data was analyzed and calculated.
[0152] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).
[0153] Before performing the measurements and analysis, the dedicated software was set up as follows.
[0154] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.
[0155] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.
[0156] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "aperture flush" function of the analysis software to remove dirt and air bubbles from inside the aperture tube. (2) About 30 ml of the electrolyte solution is placed in a 100 ml flat-bottom glass beaker. Add to the beaker a 10% by weight aqueous solution of "Contaminon N" (a pH 7 neutral detergent for cleaning precision measuring instruments, made of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) as a dispersant. Add approximately 0.3 ml of a solution prepared by diluting 100% ethanol (manufactured by Epson) three times with ion-exchanged water. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispension System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. About 2 ml of the above-mentioned Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolyte solution (5) in which the toner is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) and number average particle size (D1) are calculated. Note that when the dedicated software is set to graph / volume %, the "average diameter" on the analysis / volume statistics (arithmetic mean) screen is the weight average particle size (D4), and when the dedicated software is set to graph / number %, the "average diameter" on the analysis / number statistics (arithmetic mean) screen is the number average particle size (D1). EXAMPLES
[0157] As the carrier core particles, different types of particles were prepared as follows:
[0158] <Production Example of Magnetic Carrier Core 1 (Porous Magnetic Core Particles)> Step 1 (weighing and mixing step) Fe2O367.5% by mass MnCO329.2% by mass Mg(OH)22.0% by mass SrCO31.3% by mass The ferrite raw material was weighed, and 80 parts by mass of the ferrite raw material was mixed with 20 parts by mass of water and pulverized to prepare a slurry having a solid content of 80% by mass.
[0159] Step 2 (pre-firing step) The resulting slurry was dried using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.) and then fired in a batch-type electric furnace in a nitrogen atmosphere (oxygen concentration 1.0% by volume) at a temperature of 1030° C. for 3.0 hours to produce calcined ferrite.
[0160] Process 3 (Crushing process) The obtained calcined ferrite was crushed to about 0.5 mm with a crusher, and water was added to prepare a slurry. The solid content of the slurry was set to 70 mass %. The slurry was crushed for 3 hours with a wet ball mill using stainless steel beads with a diameter of 1 / 8 inch, and further crushed for 4 hours with a wet bead mill using zirconia with a diameter of 1 mm, to obtain a calcined ferrite slurry with a volume-based 50% particle size (D50) of 1.3 μm.
[0161] Process 4 (granulation process) To the calcined ferrite slurry, 1.0 part by mass of ammonium polycarboxylate as a dispersant and 1.5 parts by mass of polyvinyl alcohol as a binder were added per 100 parts by mass of the calcined ferrite, and the mixture was granulated into spherical particles using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.) and dried. The resulting granulated material was subjected to particle size adjustment, and then heated at 750°C for 2 hours using a rotary electric furnace to remove organic substances such as the dispersant and binder.
[0162] Step 5 (baking step) The material was fired in a nitrogen atmosphere (oxygen concentration 1.0% by volume) for 2 hours from room temperature to the firing temperature (1100°C), and then held at 1100°C for 4 hours. The material was then cooled to 60°C over 8 hours, returned from the nitrogen atmosphere to the air, and taken out at a temperature of 40°C or less.
[0163] Step 6 (sorting step) After the aggregated particles were crushed, the particles were sieved through a sieve with 150 μm openings to remove coarse particles, air classification was carried out to remove fine powder, and further magnetic separation was carried out to remove low magnetic force particles to obtain ferrite-based core material particles. The obtained ferrite-based core material particles were porous and had pores.
[0164] Process 7 (filling process) 100 parts by mass of the obtained ferrite-based core particles were placed in a stirring vessel of a mixer (Dalton's universal stirrer NDMV type), and nitrogen was introduced while maintaining the temperature at 60°C and reducing the pressure to 2.3 kPa. 50 parts by mass of methylphenyl silicone resin and 50 parts by mass of toluene were mixed for 10 minutes with a multi-blender mixer, and then dropped onto the ferrite-based core particles. The amount of dripping was adjusted so that the solid content of the resin component was 5.0 parts by mass per 100 parts by mass of the ferrite-based core particles.
[0165] After the dropwise addition was completed, stirring was continued for 2.5 hours, the temperature was then raised to 70° C., the solvent was removed under reduced pressure, and the inside of the ferrite-based core particles was filled with the above-mentioned resin composition.
[0166] After cooling, the obtained ferrite-based core material particles were transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) with a spiral blade in a rotatable mixing container, and the temperature was raised to a set temperature of 220°C at a heating rate of 2°C / min under a nitrogen atmosphere. Heating and stirring were carried out at this temperature for 1.0 hour to harden the resin, and stirring was continued for an additional 1.0 hour while maintaining the temperature at 200°C.
[0167] After that, it was cooled to room temperature, and the ferrite-based core particles filled with resin and hardened were taken out, and non-magnetic materials were removed using a magnetic separator. Furthermore, coarse particles were removed using a vibrating sieve to obtain magnetic carrier cores 1 filled with resin. The 50% particle size (D50) based on volume distribution of magnetic carrier cores 1 was 37.7 μm. The physical properties of the obtained magnetic carrier cores 1 are shown in Table 1.
[0168] <Manufacturing example of magnetic carrier core 2 (ferrite core particles)> Process 1 (weighing and mixing process) Fe2O361.7% by mass MnCO334.2% by mass Mg(OH)23.0% by mass SrCO31.1% by mass The ferrite raw material was weighed so that
[0169] Thereafter, the mixture was ground and mixed for 2 hours in a dry ball mill using zirconia balls (φ10 mm).
[0170] Step 2 (pre-firing step) After crushing and mixing, the mixture was sintered in air at 1000℃ for 2 hours in a burner-type sintering furnace to produce calcined ferrite. The composition of the ferrite is as follows: (MnO)a(MgO)b(SrO)c(Fe2O3)d In the above formula, a = 0.40, b = 0.07, c = 0.01, d = 0.52
[0171] Process 3 (Crushing process) After crushing to about 0.5 mm with a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite and crushed in a wet ball mill using stainless steel balls (φ1.0 mm) for 2 hours. After separating the balls, the mixture was crushed in a wet bead mill using stainless steel balls (φ1.0 mm) for 3 hours to obtain a ferrite slurry.
[0172] Process 4 (granulation process) To the ferrite slurry, 1.5 parts by mass of polyvinyl alcohol was added as a binder per 100 parts by mass of the calcined ferrite, and the mixture was granulated into spherical particles of 36 μm using a spray dryer (manufacturer: Okawara Kakoki).
[0173] Step 5 (Main firing step) In order to control the firing atmosphere, firing was performed in an electric furnace under a nitrogen atmosphere (oxygen concentration: 0.6% by volume) at 1200° C. for 6 hours.
[0174] Step 6 (sorting step) The aggregated particles were disintegrated, and then the mixture was sieved through a sieve having openings of 250 μm to remove coarse particles, thereby obtaining magnetic carrier cores 2. The physical properties of the obtained magnetic carrier cores 2 are shown in Table 1.
[0175] <Preparation of magnetic particles A> While passing nitrogen gas at 20 L / min through a reaction vessel equipped with a gas inlet tube, Fe 2+ 26.7L of ferrous sulfate solution containing 1.5 mol / L and Si 4+ 1.0L of 0.2 mol / L sodium silicate No. 3 aqueous solution was added to 22.3L of 3.4N sodium hydroxide aqueous solution, the pH was adjusted to 6.8, and the temperature was raised to 90°C. 1.2L of 3.5N sodium hydroxide aqueous solution was added to adjust the pH to 8.5, stirring was continued, and the gas was replaced with air and aerated at 100L / min for 90 minutes. The pH was neutralized to 7 using dilute sulfuric acid, and the resulting particles were washed with water, filtered, dried, and pulverized to obtain magnetic particles A with a number average particle size of 0.30μm.
[0176] The magnetic particles A obtained and a silane coupling agent (3-glycidoxypropylmethyldimethoxysilane) (1.2 parts by mass per 100 parts by mass of the magnetite fine particles) were introduced into a container, and the magnetic particles A were surface-treated by high-speed mixing and stirring at 100° C. for 1 hour in the container.
[0177] <Preparation of magnetic particles B> Similar to the magnetic particles A, 100 parts by mass of spherical hematite particles having a number-average particle size of 0.40 μm were subjected to surface treatment with 1.2 parts by mass of a silane coupling agent (3-(2-aminoethylamino)propyltrimethoxysilane).
[0178] <Production Example of Magnetic Carrier Core 3 (Magnetic Material Dispersed Resin Core Particles)> Phenol 10.0 parts by weight Formaldehyde solution (37% by weight formaldehyde aqueous solution) 15.0 parts by weight Surface-treated magnetic particles A 90.0 parts by weight Surface-treated magnetic particles B 10.0 parts by mass 3.5 parts by weight of 25% ammonia water ·Water 15.0 parts by mass The above materials were introduced into a reactor, heated to 40°C, and mixed thoroughly. Then, the materials were heated to 85°C at an average heating rate of 1.5°C / min while stirring, and held at 85°C for 3 hours to polymerize and harden. The peripheral speed of the stirring blades was 1.96 m / sec.
[0179] After the polymerization reaction, the mixture was cooled to 30°C and water was added. The supernatant was removed to obtain a precipitate, which was washed with water and then air-dried. The air-dried product was dried at 180°C for 5 hours under reduced pressure (5 mmHg or less) to obtain magnetic carrier cores 3, which are magnetic material-dispersed resin particles. The physical properties of the obtained magnetic carrier cores 3 are shown in Table 1.
[0180] [Table 1]
[0181] <Production Examples of Resins A-1 to A-12> Acrylic monomers corresponding to the repeating units shown in Table 2 were added in the parts by mass shown in Table 2 to a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen suction tube, and a grinding type stirrer. 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were further added. The resulting mixture was kept at 75°C for 10 hours under a nitrogen stream, and after the polymerization reaction was completed, washing was repeated to obtain resins A-1 to A-12 (solid content 30% by mass).
[0182] [Table 2-1]
[0183] [Table 2-2]
[0184] <Production Examples of Resins B-1 to B-9> Acrylic monomers corresponding to the repeating units shown in Table 3 were added in the parts by mass shown in Table 3 to a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen suction tube, and a grinding type stirrer. 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were further added. The resulting mixture was kept at 75°C for 10 hours under a nitrogen stream, and after the polymerization reaction was completed, washing was repeated to obtain resins B-1 to B-9 (solid content 30% by mass).
[0185] [Table 3]
[0186] <Production Examples of Magnetic Carriers 1 to 19> Resin A shown in Table 2 and Resin B shown in Table 3 were added to a resin solution in the combination and parts by mass shown in Table 4 below, and 400 parts by mass of toluene were added and stirred for 10 minutes using a multi-blender mixer to prepare a resin solution.
[0187] Next, 100 parts by mass of the magnetic carrier cores shown in Table 4 were mixed in a planetary mixer (Nauta Mixer VN type manufactured by Hosokawa Micron Corporation) maintained at a temperature of 60°C under reduced pressure (1.5 kPa). The resin solution was added so that the solid content of the resin component was 2.2 parts by mass. After the addition, the solvent was removed and the coating operation was carried out at a temperature of 100° C. for 50 minutes.
[0188] The magnetic carrier coated with the coating resin composition was then transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixture was heat-treated for 2 hours at 120°C in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier 1 obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified with an air classifier to obtain magnetic carrier 1.
[0189] In the same manner as in the preparation of the magnetic carrier 1, the combination of the resin solution consisting of the carrier core type, resin A, and resin B shown in Table 4 above was used, and the solid content of the resin was added to 100 parts by mass of the magnetic carrier core in the solid content ratio of the resin component shown in Table 4, and coated onto the magnetic carrier core to obtain magnetic carriers 2 to 19.
[0190] [Table 4]
[0191] <Production examples of methylphenylsilicone-coated magnetic carrier particles S, T, and U> 100 parts by mass of the magnetic carrier cores 2 were placed in a stirring vessel of a mixer (NDMV type universal stirrer manufactured by Dalton), and nitrogen was introduced while maintaining the temperature at 60° C. and reducing the pressure to 2.3 kPa.
[0192] Next, 38 parts by mass of methyl silicone oligomer, 62 parts by mass of methyl phenyl silicone oligomer, 90 parts by mass of toluene, 4 parts by mass of γ-aminopropyl triethoxysilane, and 6 parts by mass of tetraisopropyl titanate were mixed with a multi-blender mixer for 10 minutes to prepare a coating liquid. Next, the coating liquid was dropped while mixing so that the resin solid content was 1.2 parts by mass per 100 parts by mass of magnetic carrier core 2.
[0193] After the dropwise addition was completed, stirring was continued for 2.5 hours, the temperature was then raised to 100° C., and the solvent was removed under reduced pressure.
[0194] After cooling, the mixture was transferred to a mixer equipped with a spiral blade (a drum mixer type UD-AT manufactured by Sugiyama Heavy Industries Co., Ltd.) and heated to a set temperature of 180°C at a heating rate of 2°C / min under a nitrogen atmosphere, and heated and stirred at this temperature for 2.0 hours to obtain magnetic carrier particles S coated with methylphenyl silicone.
[0195] Similarly, a resin solution prepared using the parts by mass of methyl silicone oligomer and parts by mass of methyl phenyl silicone oligomer shown in Table 5 was used to obtain magnetic carrier particles T and magnetic carrier particles U coated in the same manner as magnetic carrier particles S.
[0196] [Table 5]
[0197] <Production Example of Magnetic Carrier 20> Resin solution A-13 was prepared by adding 400 parts by mass of toluene to 100 parts by mass of resin A-13 shown in Table 6 and stirring for 10 minutes with a multi-blender mixer.
[0198] The magnetic carrier particles S were added to a planetary mixer (Nauta Mixer VN type manufactured by Hosokawa Micron Corporation) maintained at a temperature of 60° C. under reduced pressure (1.5 kPa), and resin solution A-13 was added so that the solid content of the resin component was 0.3 parts by mass per 100 parts by mass of the magnetic carrier core. After addition, the solvent was removed and the coating operation was carried out at a temperature of 100° C. for 50 minutes.
[0199] Thereafter, the magnetic carrier coated with the coating resin composition was transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixture was heat-treated at a temperature of 160°C for 2 hours in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified by an air classifier to obtain magnetic carrier 20.
[0200] <Production Example of Magnetic Carrier 21> A monomer corresponding to the repeating unit shown in Resin A-14 in Table 6 was mixed with 90 parts by mass of toluene, 6 parts by mass of γ-aminopropyltriethoxysilane, and 4 parts by mass of tetraisopropyl titanate and stirred in a multi-blender mixer for 10 minutes to prepare coating solution A-14. The magnetic carrier particles T were charged into a planetary mixer (Nauta Mixer VN type manufactured by Hosokawa Micron Corporation) maintained at a temperature of 60° C. under reduced pressure (1.5 kPa), and the coating solution A-14 was dripped into the magnetic carrier cores so that the resin component solid content was 0.3 parts by mass per 100 parts by mass of the magnetic carrier cores. After the charging, the solvent was removed and the coating operation was carried out at a temperature of 100° C. for 50 minutes.
[0201] The magnetic carrier coated with the coating resin composition was then transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixture was heat-treated for 2 hours at 250°C in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier thus obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified by an air classifier to obtain magnetic carrier 21.
[0202] <Production Example of Magnetic Carrier 22> 0.3 parts by mass of fluororesin (microparticulated to 0.1 μm) having the repeating unit shown in Resin A-15 in Table 6 was added to a planetary mixer for 1.2 parts by mass of magnetic carrier particles U10, and stirred for 50 minutes. The obtained magnetic particles were coated using a fluidized bed coating device at a temperature of 360° C. for 2 hours to obtain magnetic carrier 22.
[0203] <Manufacturing example of magnetic carrier 23> Resin A-16 shown in Table 6 and Resin B-8 shown in Table 3 were added to a resin solution in the combination and parts by mass shown in Table 7, and 400 parts by mass of toluene were added and stirred for 10 minutes using a multi-blender mixer to prepare a resin solution.
[0204] Next, the resin solution was added to a planetary mixer (Nauta Mixer VN type manufactured by Hosokawa Micron Corporation) maintained at a temperature of 60°C under reduced pressure (1.5 kPa) so that the resin component solid content was 1.5 parts by mass per 100 parts by mass of the magnetic carrier cores shown in Table 7. After addition, the solvent was removed and the coating operation was carried out at a temperature of 100°C for 50 minutes.
[0205] The magnetic carrier coated with the coating resin composition was then transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixing container was rotated 10 times per minute while stirring, and heat-treated at a temperature of 160°C for 4 hours in a nitrogen atmosphere. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified with an air classifier to obtain magnetic carrier 23.
[0206] [Table 6-1]
[0207] [Table 6-2]
[0208] [Table 7]
[0209] <Toner 1 Manufacturing Example> Polyester resin 100 parts by weight Fischer-Tropsch wax (maximum endothermic peak temperature 90°C) 4 parts by mass 0.1 parts by weight of 3,5-di-t-butylsalicylic acid aluminum compound (Bontron E88, manufactured by Orient Chemical Industry Co., Ltd.) CI Pigment Blue 15:3 4.5 parts by weight The above materials were mixed using a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 1500 rpm for a rotation time of 5 min, and then kneaded using a twin-screw kneader (PCM-30, manufactured by Ikegai Co., Ltd.) set at a temperature of 130°C. The kneaded product obtained was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product obtained was finely crushed using a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a Faculty (F-300, manufactured by Hosokawa Micron Corporation), and toner base particles 1 were obtained. The operating conditions were a classification rotor rotation speed of 11000 rpm and a dispersion rotor rotation speed of 7200 rpm.
[0210] Toner base particles 1 100 parts by weight Silica fine particles A (number average particle size (D1) is 120 nm) 2.0 parts by weight The raw materials shown in the above recipe were mixed using a Henschel mixer (FM-10C type, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 3 minutes, and then heat-treated using the surface treatment device shown in Figure 3 to obtain heat-treated toner particles 1. The operating conditions were feed rate = 5 kg / hr, hot air temperature = 160°C, and hot air flow rate = 6 m 3 / min., cold air temperature = -5℃, cold air flow rate = 4m 3 / min., Blower air volume = 20m 3 / min., Injection air flow rate = 1m 3 / min.
[0211] The obtained heat-treated toner particles were classified by an inertial classification system using an Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.) to obtain heat-treated toner particles. Heat-treated toner particles 1 100 parts by weight Silica fine particles B (number average particle size (D1) is 20 nm) 0.6 parts by mass The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 3 minutes to obtain Toner 1 (weight average particle diameter 6.0 μm).
[0212] [Examples 1 to 17] 9 parts by mass of toner 1 was added to 91 parts by mass of magnetic carrier 1, and the mixture was shaken with a shaker (YS-8D type: manufactured by Yayoi Co., Ltd.) to prepare 320 g of two-component developer 1. The vibration conditions of the shaker were 150 rpm and 2 minutes.
[0213] On the other hand, 90 parts by mass of toner 1 was added to 10 parts by mass of magnetic carrier 1, and mixed for 5 minutes in a V-type mixer in an environment of normal temperature and humidity of 23° C. / 50% RH to obtain refill developer 1.
[0214] The two-component developer 1 and the replenishing developer 1 were used for the following evaluation.
[0215] A modified imagePRESS C800 (Canon) was used as the image forming apparatus, and two-component developer 1 was placed in the developer unit at the cyan position, and a replenishment developer container containing replenishment developer 1 was set. The modifications were made so that the DC voltage VDC of the developer carrier, the charging voltage VD of the electrostatic latent image carrier, the laser power, and the total discharge current of the charger could be freely set.
[0216] For image output evaluation, an FFH image (solid image) with the desired image ratio was output, and the VDC, VD, and laser power were adjusted so that the toner amount of the FFH image was the desired amount, and the evaluation described below was performed. FFH is a value that expresses 256 gradations in hexadecimal, with 00h being the 1st gradation (white background) of the 256 gradations, and FFH being the 256th gradation (solid area) of the 256 gradations.
[0217] The process speed was set to 357 mm / s, and the total discharge current of the charger was set to 100 μA. 2 ) (sold by Canon Marketing Japan Inc.) was used.
[0218] [Evaluation X: In-plane stability of image density after long-term use] After printing 40,000 sheets of FFH output charts with an image area ratio of 70% at 23°C and 50% RH (hereinafter referred to as N / N environment), we printed 10 sheets of "96H output charts with an image area ratio of 100% (A4 full-face halftone image)".
[0219] The reflection density was determined by measuring the image density using a spectrodensitometer 500 series (manufactured by X-Rite).
[0220] The measurement site is Three points: 0.5 cm from the tip of the image (the part printed first), 5.0 cm, 15.0 cm, and 25.0 cm from the left edge of the image (the part printed first is considered the top). Three points: 7.0 cm from the tip of the image, 5.0 cm, 15.0 cm, and 25.0 cm from the left edge of the image. Three points: 14.0 cm from the tip of the image, 5.0 cm, 15.0 cm, and 25.0 cm from the left edge of the image. Three points: 20.0 cm from the tip of the image, 5.0 cm, 15.0 cm, and 25.0 cm from the left edge of the image. A total of 12 points were scored, and the difference between the highest and lowest image densities was calculated. The sheet with the largest difference in density among the 10 sheets was taken as the evaluation result. The evaluation criteria were as follows: A (10 points): Less than 0.030 B (9 points): 0.030 or more and less than 0.040 C (8 points): 0.040 or more and less than 0.050 D (7 points): 0.050 or more and less than 0.060 E (6 points): 0.060 or more and less than 0.070 F (5 points): 0.070 or more and less than 0.080 G (4 points): 0.080 or more and less than 0.090 H (3 points): 0.090 or more and less than 0.100 I (2 points): 0.100 or more and less than 0.110 J (1 point): 0.110 or more
[0221] For the X rating, a score of 7 or above was considered a passing grade.
[0222] [Evaluation Y: Image density stability after long-term use in a high humidity environment] At 32°C and 80% RH (hereinafter referred to as H / H environment), 4000 sheets of a chart with an image area ratio of 70% FFH output were printed, and then 4000 sheets of a chart with an FFH output of 5% were printed. The above image output was carried out five times (a total of 40,000 sheets were printed), and immediately after passing the 40,000 sheets, image A with the density set as shown below was printed.
[0223] The electron microscope was then turned off and left in a H / H environment for 168 hours (7 days), after which the power to the main unit was turned on again and image A was output. Pattern 1: 0.10~0.13 Pattern 2: 0.25~0.28 Pattern 3: 0.40~0.43 Pattern 4: 0.55~0.58 Pattern 5: 0.70~0.73 Pattern 6: 0.85~0.88 Pattern 7: 1.00~1.03 Pattern 8: 1.15~1.18 Pattern 9: 1.30~1.33 Pattern 10: 1.45~1.48
[0224] The criteria for judgment are as follows: A (10 points): All pattern images meet the above density range. B (9 points): One pattern image falls outside the above density range. C (8 points): The two pattern images are outside the above density range. D (7 points): Three pattern images are outside the above density range. E (6 points): Four pattern images are outside the above density range. F (5 points): Five pattern images are outside the above density range. G (4 points): Six pattern images are outside the above density range. H (3 points): Seven pattern images are outside the above density range. I (2 points): Eight pattern images are outside the above density range. J (1 point): Nine or more pattern images are outside the above density range.
[0225] For evaluation Y, a score of 8 or above was considered a passing grade.
[0226] [Rating Z: Carrier flying after long-term use in low humidity environment] At 23°C and 5% RH (hereafter referred to as N / L environment), 4,000 sheets of a chart with an image area ratio of 70% FFH output were printed, followed by 4,000 sheets of a chart with an FFH output of 5%. After printing the above image five times (a total of 40,000 sheets), 100 sheets of "FFH output chart with an image ratio of 100% (A3 full solid image)" were printed while adjusting the toner supply so that the toner concentration in the two-component developer was 6% by mass.
[0227] After that, in the same way, the power was turned off halfway through printing a "FFH output chart with 100% image ratio (A3 full-page solid image)," and the toner developed on the electrostatic latent image carrier before cleaning was sampled by pressing a transparent adhesive tape against it. At that time, any toner that could not be removed in one go was sampled again with the transparent adhesive tape, and this was repeated until all the toner on the electrostatic latent image carrier was gone.
[0228] The number of magnetic carrier particles adhering to the electrostatic latent image carrier within a 1 cm × 10 cm area on the adhesive tape was counted. 2 The number of carrier particles adhering per unit was calculated and evaluated according to the following criteria. A (10 points): 10 or less B (9 points): 11 or more and 15 or less C (8 points): 16 or more and 20 or less D (7 points): 21 or more and 25 or less E (6 points): 26 or more and 30 or less F (5 points): 31 or more and 35 or less G (4 points): 36 or more and 40 or less H (3 points): 41 or more and 45 or less I (2 points): 46 or more and 50 or less. J (1 point): 51 or more
[0229] For the Z rating, a score of 7 or above was considered a passing grade.
[0230] Additionally, a total score of 22 or above for each evaluation was considered a passing grade.
[0231] In Examples 2 to 17, similarly to Example 1, two-component developers and replenishment developers were prepared using the combinations of magnetic carrier and toner 1 shown in Table 8, and evaluations were performed in the same manner as in Example 1. The evaluation results are shown in Table 9.
[0232] [Comparative Examples 1 to 6] In Comparative Examples 1 to 6, similarly to Example 1, two-component developers and replenishment developers were prepared using the combinations of magnetic carrier and toner 1 shown in Table 8, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 9.
[0233] [Table 8]
[0234] [Table 9]
Claims
1. A magnetic carrier having a magnetic carrier core and a coating resin layer that coats the surface of the magnetic carrier core, The coating resin layer contains a resin A and a resin B, Based on the total resin components constituting the coating resin layer, the content of the resin A is 1.0% by mass or more and 50.0% by mass or less, and the content of the resin B is 50.0% by mass or more and 99.0% by mass or less, The resin A is The main chain and a first side chain bonded to the main chain and having a partial structure represented by any one of formulas (1) to (3); a second side chain attached to the backbone; and It has When the total mass of the first side chains in the resin A is a1 and the total mass of the second side chains is a2, the a1 and a2 are 0.02≦a1 / a2≦2.00 Fulfilling When the SP value of the first side chain is SPa1, the SP value of the second side chain is SPa2, and the SP value of the resin B is SPb1, the SPa1, SPa2, and SPb1 are 1.3<SPa2-SPa1≦7.0 1.3<SPb1-SPa1≦7.0 0.0≦|SPa2-SPb1|≦1.3 A magnetic carrier comprising: 【Chemistry 1】 (In the above formula (1), R 1 represents a hydrogen or a methyl group. X 1 represents "COO" or "O". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less. 【Chemistry 2】 (In the above formula (2), R 11 "OCH 3 " or "O.C. 2 H 5 " or "CH 3 ". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less. 【Chemistry 3】 (In the above formula (3), R 13 indicates "F" or "H". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less.
2. 2. The magnetic carrier according to claim 1, wherein the repeating unit of the first side chain having the structure represented by formula (1) of the resin A has any one of the structures represented by formulas (1-1) to (1-4). 【Chemistry 4】 (In the above formulas (1-1) to (1-4), R 1 represents a hydrogen or a methyl group. X 1 represents "COO" or "O". R 21 represents a single bond or an alkylene group. R 22 represents an alkylene group having a branched structure formed by a carbon-carbon bond. Rf 11 represents a monovalent group having at least a fluoroalkyl group Rf 12 represents a fluoroalkyl group having a tertiary or quaternary carbon. Rf 13 represents a perfluoroalkyl group having 4 to 6 carbon atoms.)
3. 3. The magnetic carrier according to claim 1, wherein the second side chain of the resin A has a partial structure represented by the following formula (4), and the resin B contains a resin including a partial structure represented by the following formula (5). 【Chemistry 5】 (R 3 "H" or "CH 3 ". R 4 represents a divalent organic group. X 2 represents a polymer having, as a polymerization component, one or more compounds selected from the group consisting of a hydrocarbon group having 6 to 1,000 carbon atoms, or an acrylic acid ester, a methacrylic acid ester, styrene, and acrylonitrile. 【Chemistry 6】 (R 5 "H" or "CH 3 ", Y represents a hydrocarbon group having 1 to 12 carbon atoms, "COOH", or "COOR 6 " and R 6 represents a hydrocarbon group having 1 to 12 carbon atoms.
4. The second side chain of the resin A has a partial structure represented by the following formula (4), 4. The magnetic carrier according to claim 1, wherein the main chain of the resin A has a partial structure represented by the following formula (6): 【Chemistry 7】 (R 3 "H" or "CH 3 ". R 4 represents a divalent organic group. X 2 represents a polymer having, as a polymerization component, one or more compounds selected from the group consisting of a hydrocarbon group having 6 to 1,000 carbon atoms, or an acrylic acid ester, a methacrylic acid ester, styrene, and acrylonitrile. 【Chemistry 8】 (R 7 "H" or "CH 3 ", Z represents a hydrocarbon group having 1 to 12 carbon atoms, "COOH", or "COOR 8 " and R 8 represents an alkyl group having 1 to 12 carbon atoms.
5. The first side chain of the resin A has a partial structure represented by the following formula (2), The second side chain of the resin A has a partial structure represented by the following formula (7), 2. The magnetic carrier according to claim 1, wherein the resin B contains a resin containing a partial structure represented by the following formula (5): 【Chemistry 9】 (In the above formula (2), R 11 "OCH 3 " or "O.C. 2 H 5 " or "CH 3 ". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less. 【Chemistry 10】 (In the above formula (7), R 9 Or R 10 "CH 3 " or "C 6 H 5 ".)
6. The first side chain of the resin A has a partial structure represented by the following formula (3), The second side chain of the resin A has a partial structure represented by the following formula (7), 2. The magnetic carrier according to claim 1, wherein the resin B contains a resin containing a partial structure represented by the following formula (7): 【Chemistry 11】 (In the above formula (3), R 13 indicates "F" or "H". R 2 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group being a halogen-substituted alkyl group in which at least a portion of hydrogen atoms are substituted with fluorine atoms, and a portion of the remaining hydrogen atoms may be substituted with halogen atoms other than fluorine atoms, Based on the total number of hydrogen atoms, fluorine atoms, and halogen atoms other than fluorine atoms contained in the alkyl group, the proportion of fluorine atoms is 5.0 atomic % or more, and the proportion of halogen atoms other than fluorine atoms is 40.0 atomic % or less. 【Chemistry 12】 (In the above formula (7), R 9 Or R 10 "CH 3 " or "C 6 H 5 ".)
7. When the SP value of the second side chain is SPa2 and the SP value of the resin B is SPb1, the SP2 and SPb1 are 0.0≦|SPa2-SPb1|≦1.1 7. The magnetic carrier according to claim 1, which satisfies the above condition.
8. 8. The magnetic carrier according to claim 1, wherein the content of the coating resin is 0.2 parts by mass or more and 5.0 parts by mass or less based on 100 parts by mass of the magnetic carrier core.
9. A magnetic carrier described in any one of claims 1 to 8, wherein the total resin components are resin A and resin B.
10. A two-component developer comprising the magnetic carrier according to any one of claims 1 to 9 and a toner.
11. A refill developer comprising the magnetic carrier according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carrier for electrophotographic dry type toner
JP1978097435A
Electrostatic image developing carrier
JP1988235963A
Developer for electrostatic image
JP1990186360A
Electrostatic latent image developing carrier, its production, electrostatic latent image developer and image forming method
JP1997319155A
Two-component developer
JP2017134333A